Análise de Handover inter e intra-célula em um sistema de telefonia celular através de método de medição simplificado - Sales, Diego Fernandes (2009)
This dissertation has the purpose to present a portable device named PlugData MG100G, equipped with a cellular module, to analyze the radiofrequency coverage in a GSM network situated in João Pessoa city, state of Paraíba, at four distinct regions. The equipment, originally, was developed to be used in fixed environments, so it was adapted so that it could be used in conditions of mobility. From the Mobile Measurement Reports (MMRs) RF coverage and the handover process are analyzed. The MMRs enable the identification of the serving cell and the list of the closest neighboring cells monitored by the mobile. This work analyses only data referent to the serving cell and the two closest neighboring cells. Inter-cell and intra-cell handovers are identified. The frequency planning and quality of service offered by the network related to the regions are discussed as well